2020
DOI: 10.1007/s11270-020-04770-0
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Impact of Land Cover and DEM Resolution on the Accuracy of Computed Streamflow Using the SWAT Model

Abstract: Twenty daily time step-based SWAT simulation models for the Duhok, Adhaim and Dokan dam watersheds, in Iraq, were implemented using five land cover (LC) and digital elevation model (DEM) of different resolutions. The optimal LC and DEM for computing the most accurate streamflow for each watershed were specified. Results indicated that delineation of the flat watersheds is significantly affected by the DEM resolution and there was no evident trend on the computation of watersheds' total areas, boundaries, numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…SWAT is a semi-distributed, physically based hydrological model operated in QGIS through the QSWAT extension. SWAT is a globally employed and efficient tool for quantifying various hydrological components, such as surface runoff, sediments, and pollution (Al-Khafaji et al 2020). The flowchart in Fig.…”
Section: Hydrological Modellingmentioning
confidence: 99%
“…SWAT is a semi-distributed, physically based hydrological model operated in QGIS through the QSWAT extension. SWAT is a globally employed and efficient tool for quantifying various hydrological components, such as surface runoff, sediments, and pollution (Al-Khafaji et al 2020). The flowchart in Fig.…”
Section: Hydrological Modellingmentioning
confidence: 99%
“…The ARB has an area of 11600 km 2 , one of Tigris River's tributaries. The ARB Figure 1 is located between the longitudes 43° 41′ 9″ to 45° 27′ 31″ E and latitudes 35° 42′ 24″ to 34° 33′ 8″ N in northern Iraq [33]. The river originates from highlands of 1800 meters above sea level (m.a.s.l.)…”
Section: Study Areamentioning
confidence: 99%
“…The Shuttle Radar Topography Mission (SRTM) Digital Elevation Models (DEMs) of 90 m spatial resolution were used in SWAT for watershed delineation and determination of stream locations (downloaded from; http://glcf.umd.edu/data/srtm/, access date 30/4/2021). The Moderate Resolution Imaging Spectroradiometer (MODIS) land cover/use of 500 m spatial resolution (downloaded from; http://gdex.cr.usgs.gov/gdex/, access date 10/4/2021) and Food and Agriculture Organization (FAO) soil data of 1:500000 spatial scale (downloaded from; https://www.fao.org, access date 22/4/2021) were used in defining Hydrologic Response Units in SWAT [33]. Figure 2 shows the spatial data used in the SWAT model.…”
Section: Datamentioning
confidence: 99%
“…In recent years, the sensitivity of the SWAT model to spatial input data has attracted the attention of researchers [6,8,[11][12][13]. The previous studies show somewhat contradicting results, and there is no clear pattern indicating that high-resolution and local data outperform the low-resolution data.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Geza and McCray [14] evaluated the performance of SWAT with two U.S. soils (i.e., high-resolution SSURGO and low-resolution STATSGO soils) and reported better performance of the model with SSURGO soil. Al-Khafaji et al [12] investigated the effect of DEM and land use data quality on the accuracy of SWAT model predictions and reported that high-resolution datasets did not provide better predictive reliability. Similar results were obtained by Asante et al [11], who evaluated the impact of land use data quality on the predictive capacity SWAT model and indicated slightly better performance of low-resolution land use data.…”
Section: Introductionmentioning
confidence: 99%